Secondary Traumatic Stress in the Courtroom: Suggestions for Preventing Vicarious Trauma Resulting from Child Sexual Abuse Imagery. (6th June 2019) - Polak, Shely; Bailey, Rebecca; Bailey, Elizabeth
Abstract: The internet and social media have added to an increase in sexual imagery. As a result, law enforcement, judicial officers and court ordered counselors will be exposed to an increase of images. While not every individual will experience post‐traumatic stress symptoms, it is anticipated there is risk for impact. The impact of viewing images can include an increase in vicarious trauma symptoms, burnout, and a possible decrease in impartiality. This paper offers suggestions for self‐care in the services of preventing collateral damage.